Biodiversity Indices of Mangrove Community in Gili Sulat, East Lombok - Diniyatushoaliha, Ainun; Al Idrus, Agil; Bahri , Syamsul (Jurnal Biologi Tropis, 2024)
Mangrove ecosystems play an important role in supporting environmental stability, providing ecological services, and influencing the long-term survival of many living organisms. This research aims to analyse the biodiversity indices of mangrove community in Gili Sulat, East Lombok. The method for determining stations is based on purposive sampling. Each station has three plots. The method for determining plots is based on mangrove density (sparse, moderate, dense). Data were collected using plots of 10x10 m2 for trees, 5x5 m2 for saplings, and 2x2 m2 for seedlings. Diversity, richness, evenness, and dominance values were calculated using the Shannon-Weaver diversity index (H’), Margalef-Richness index (R), Pielou-Evenness index (E), and Simpson-Dominance index (D) to calculate. The results showed twelve mangrove species in tree, sapling, and seedling categories. The diversity index in three stations ranges from low to moderate, the richness index shows species richness of mangrove is low, the evenness index shows that mangrove species evenness ranges from low and high, the dominance index shows that mangrove species dominance range from low and high. Thus, these results present that biodiversity indices of mangrove community in Gili Sulat are: (1) the diversity index (1,73) presents that species diversity and ecolocigal pressure are moderate, (2) the richness index (1,78) presents that species richness is low, (3) the evenness index (0,70) presents that species evenness is moderate and ecosystem condition is less stable, (4) the dominance index (0,26) presents that species dominance is low and almost no species dominate.